Pattern recognition : 7th Mexican Conference, MCPR 2015, Mexico City, Mexico, June 24-27, 2015, Proceedings /: 7th Mexican Conference, MCPR 2015, Mexico City, Mexico, June 24-27, 2015, Proceedings. (2015) - Unknown
No abstract available